Dimensions and Factors of Civil Servants Policy Alienation: Case of the Lithuanian State Employment Agency - Gončiarova Natalja; Pivoras, Saulius (Politologija, 2020)
The article aims to identify the dimensions and factors of policy alienation that have a significant impact on the practice of civil servants when implementing employment policy. The data of the empirical research revealed that civil servants experience powerlessness due to the following factors: insufficient coherence of employment policy objectives with objectives of other social and welfare policies, lack of interinstitutional cooperation, and autonomy in implementing internal institutional requirements. Meanwhile, the factors of meaninglessness are related to red tape and categories, as distinguished by informants, of unemployed clients, whose expectations are incommensurable with the aims and means of implemented employment policy.